An Overview of the Current State and Prospects for Oil Recovery from Oily Sludge - Chinakulova Aigerim Nurlankyzy; Niyazbekova Rimma Kalmanbayevna; Khaldun Mohammad Al Azzam; Mukhambetov Gabit Mukhambetovich; Aimagambetova Raushan Zhanatovna; El-Sayed Negim; Serekpayeva Mira (Indonesian Journal of Chemistry, 2023)
Oily sludge is a solid emulsified waste created by the petroleum industry. Solid particles, crude oil, and water comprise most of their composition. Because it contains high concentrations of cycloalkanes, benzene series, polycyclic aromatic hydrocarbons, and other harmful and hazardous substances, it poses a severe risk to human health and the environment. It must be treated to reduce its toxicity. However, crude oil is a significant component of oily sludge and has a high recycling value. As a result, numerous procedures for extracting crude oil from oily sludge have been developed, including solvent extraction, pyrolysis, centrifugation, ultrasonic treatment, electronic treatment, flotation, supercritical treatment, and combination processes. The primary purpose of this review is to describe the evolution of various recycling technologies and to compare their benefits, drawbacks, and ways of action. This concept is expected to be the cornerstone for future recycling technology development.